2022
DOI: 10.1371/journal.pone.0264981
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic development of the upper airway during the first five years of life: A three-dimensional imaging study

Abstract: Purpose Normative data on the growth and development of the upper airway across the sexes is needed for the diagnosis and treatment of congenital and acquired respiratory anomalies and to gain insight on developmental changes in speech acoustics and disorders with craniofacial anomalies. Methods The growth of the upper airway in children ages birth to 5 years, as compared to adults, was quantified using an imaging database with computed tomography studies from typically developing individuals. Methodological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Airway maintenance is a crucial step in all emergency protocols [10]. The airway volume increases with age, as stated by Chuang et al and Abramson et al [19,29], who evaluated the airway changes with growth using CT scans. In this study, a positive correlation was also found between age and all levels of airway volume (Table 4).…”
Section: Airway Volume Compared To Previous Studiesmentioning
confidence: 99%
“…Airway maintenance is a crucial step in all emergency protocols [10]. The airway volume increases with age, as stated by Chuang et al and Abramson et al [19,29], who evaluated the airway changes with growth using CT scans. In this study, a positive correlation was also found between age and all levels of airway volume (Table 4).…”
Section: Airway Volume Compared To Previous Studiesmentioning
confidence: 99%